FAILURE ANALYSIS OF CHANNEL 1 MONOPULSE SECONDARY SURVEILLANCE RADAR IRS 20 MPS - Raihan Muhammad Farid; Faridh Surya Pratama; Mayang Enggar Kusumastuti (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2023)
Radio Detection and Ranging (Radar) is an electromagnetic wave used to monitor the movement of a moving object. RADAR will get information about the height and distance of an object by utilizing electromagnetic waves. Radar is surveillance equipment to monitor the aircraft’s position in the environment around the radar up to a radius of ± 250 NM. This article aims to analyze the surveillance facility at Kualanamu Airport Monopulse Secondary Surveillance Radar (MSSR) INDRA. This paper uses an exploratory study method with descriptive qualitative research to investigate and trace the problem. The problem on the INDRA IRS 20 MPS Radar is offline due to PLN supply maintenance activities, causing the supply voltage on the radar to be unstable. The failure problem on MSSR is due to damage to the Sum Amplifier Unit (SAU) module, which causes the SUM output on the Radar to be abnormal. The result of channel 1 INDRA IRS Radar 20 MPS operation can operate again after replacing a new SAU module. The conclusion of the operation of channel 1 INDRA IRS Radar 20 MPS can operate normally again after the replacement of a new SAU module.